Inflammatory responses at the boundary between the host and the world beyond: the dilemma of infection versus colonization from a tonsillar perspective - Sarmiento Varon, Lindybeth (2020)
Obstructive sleep apnoea (OSAS) is a syndrome suffered by children with hypertrophied tonsils. We have previously demonstrated that these tonsils present a defective Breg compartment. Here, we extend those findings by evidencing the inflammatory cytokine pattern of tonsillar mononuclear cells (TMC) and investigating the grounds of such profile. OSAS TMC were the only cells used for this work. We showed the ability of Bcs to promote the loss of immune homeostatic control by promptly producing TNFα. Using FACS, we determined TNFα production by stimulated TMC in culture. Upon 24 hours, Bcs represented the majority of TNFα+ cells (52,4% ± SEM 4,2% CD20+/down cells vs 41,7% ± SEM 4,0% CD3+ cells, p < 0.05). Conversely, at the same time point, IL17 was produced primarily by CD4+ T cells (Th17) which comprised 90% of the IL17+ population. Also at 24 hs post stimulation, two thirds of the Th17 population (59% ± SEM 4%) co-expressed TNFα. Despite the pro-inflammatory profile displayed by TMC in culture, OSAS has long been considered of non-infectious etiology. We cultured the core tonsillar tissue of 31 children and identified 89 bacterial species by MALDI-TOF MS. The species identified had been previously found either causing ENT pathology or as harmless local flora, both situations in competent hosts. Pathogens differ from commensals in being able to penetrate the epithelial barriers. Hence, we performed fluorescence in situ hybridization (FISH) with a universal eubacterial (EUB338) probe followed by immune-fluorescence staining, on cryo-sections from excised tonsils. By confocal microscopy, we confirmed bacterial presence within the lymphoid compartment from OSAS biopsies. To conclude, while we cannot ascertain that the microorganisms detected in situ as well as through culture are the initiators of the ongoing inflammatory response characteristic of OSAS, the chronification of the process must be related to the evidenced bacterial spreading beyond the normal boundaries.